Application of Monoclonal Antibodies Developed Against the IpaJ Protein for Detection of Chickens Infected With Salmonella enterica Serovar Pullorum Using Competitive ELISA - Yin, Kequan; Ren, Jingwei; Zhu, Yue; Xu, Lijuan; Yin, Chao; Li, Yang; Yuan, Yu; Li, Qiuchun; Jiao, Xinan (Frontiers in Veterinary Science, 2019)
Pullorum disease remains an epidemic in the poultry industry in China. The causing pathogen is a host-restricted Salmonella enterica serovar Pullorum, which can spread through both horizontal and vertical transmissions. To eradicate the pullorum disease from poultry farms, it is necessary to specifically monitor the prevalence of the bacterial infection in adult chicks. In this study, we constructed a new competitive ELISA method based on the development of monoclonal antibodies (MAbs) against a specific immunogen of S. Pullorum, IpaJ protein. In total, eight MAbs against IpaJ were prepared using the purified recombinant His-IpaJ protein as the immunogen. Characterization of the eight MAbs demonstrated that 4G5 can be used as the competitive antibody in ELISA. A competitive ELISA was subsequently developed using purified MBP-IpaJ as the capture (0.5 μg/ml) and the HRP-labelled 4G5 (0.14 μg/ml) as the competitive antibody, respectively. A specificity test demonstrated that the ELISA assay can differentiate antisera of S. Pullorum-infected chickens from that of S. Gallinarum and S. Enteritidis. Furthermore, four out of 200 clinical antisera collected from a poultry farm were detected to be S. Pulloram positive using this method. The plate agglutination test (PAT) and the previously established indirect ELISA confirmed that these positive antisera reacted specifically with S. Pullorum. We propose that the established competitive ELISA assay based on MAb against IpaJ protein, is a novel and quick method that can detect S. Pullroum infection in the poultry industry.